Autoclaved aerated concrete material and preparation method thereof
By using graphene oxide to load calcium carbonate and graphene oxide in autoclaved aerated concrete, a nanoneedle-shaped multi-stage micro-nano structure is formed, which solves the cracking problem caused by drying and shrinkage of autoclaved aerated concrete and improves the durability of the material and mechanical properties reduce water absorption.
Patent Information
- Application Number
- CN202411268059.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-31
AI Technical Summary
The walls are prone to cracking due to the large dryness and shrinkage of the autoclaved concrete, especially in an environment with large temperature difference, the risk increases.
Graphene oxide is loaded with calcium carbonate and graphene oxide, and by producing nanoneedle-shaped multi-stage micro-nano structures, it fills capillary pores and micropores, reduces the drying and shrinking pressure difference, avoids the appearance of meniscus, and reduces the gravity between the particles. , blocking the particle distance, thereby reducing drying shrinkage.
It effectively solves the problem of wall cracking caused by drying and shrinkage, improves the durability and service life of the material, enhances the density and mechanical properties, and reduces the water absorption rate.
Smart Images

Figure CN119219373A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of new building materials, and in particular to an autoclaved aerated concrete material and a preparation method thereof. Background Art
[0002] In recent years, with the increasing efforts of my country to innovate the production technology of wall materials and the strengthening of people's environmental awareness, low-pollution and low-consumption autoclaved aerated concrete has gradually replaced traditional wall materials and become a research hotspot. Compared with ordinary concrete and clay bricks, autoclaved aerated concrete has the advantages of light weight, thermal insulation, sound insulation and noise reduction. It is a low-energy and environmentally friendly green wall material.
[0003] The autoclaved aerated concrete of the related technology uses industrial waste fly ash as the main raw material, but this autoclaved aerated concrete has a large drying shrinkage, which makes the wall easy to crack, especially when the temperature difference is large, the risk of wall cracking is greatly increased. Summary of the invention
[0004] The embodiment of the present application provides an autoclaved aerated concrete material and a preparation method thereof, wherein the material has low drying shrinkage performance and can effectively solve the problem of wall cracking caused by drying shrinkage. The technical solution is as follows:
[0005] In one aspect, an autoclaved aerated concrete material is provided, wherein the autoclaved aerated concrete material comprises the following components in parts by weight:
[0006] 45-65 parts of fly ash, 3-10 parts of gypsum, 15-25 parts of solid waste slurry, 7-10 parts of cement, 9-13 parts of lime, 0.02-0.08 parts of aluminum paste, 0.001-0.005 parts of graphene oxide loaded with calcium carbonate, 0.001-0.005 parts of graphene oxide, and 0.005-0.01 parts of silicon powder.
[0007] In a possible implementation, the size of the graphene oxide is 800 nm to 200 nm.
[0008] On the other hand, a method for preparing an autoclaved aerated concrete material is provided, the preparation method comprising:
[0009] preparing graphene oxide;
[0010] Based on the graphene oxide, preparing graphene oxide-loaded calcium carbonate;
[0011] According to the weight proportion of each component, fly ash, gypsum and solid waste slurry are wet-grinded to obtain fly ash slurry, gypsum slurry and solid waste slurry;
[0012] Turn on the pouring mixer to preheat with steam, add the fly ash slurry, the gypsum slurry and the solid waste slurry, then add the graphene oxide-loaded calcium carbonate and the graphene oxide, stir evenly, then add cement, lime, aluminum powder paste and silicon powder, stir evenly to obtain autoclaved aerated concrete slurry, and pour the autoclaved aerated concrete slurry into a mold;
[0013] A steel mesh cage is placed in the mold, and the autoclaved aerated concrete material is obtained through gasification pre-curing, cutting, and autoclaving.
[0014] In a possible implementation, the method for preparing graphene oxide includes:
[0015] 30 mL of concentrated sulfuric acid and 1 g of graphite were placed in a three-necked flask, and the reaction temperature was controlled to be no higher than 5° C. by an ice bath. A mixture of 12 g of potassium permanganate and 3 g of sodium nitrate was added to the three-necked flask, and the mixture was reacted for 2 h, and then the temperature was raised to 60° C., and the reaction was continued at 60° C. for 9 h.
[0016] Add 150 mL of deionized water to the three-necked flask, raise the temperature to 85° C., and maintain for 30 min, then lower the reaction temperature to 40° C., and drop 8 mL of hydrogen peroxide to obtain a mixed solution;
[0017] After the mixed solution turns into golden yellow, centrifugal precipitation and washing are performed until the pH value is 6.5-7.0 to obtain the graphene oxide.
[0018] In another possible implementation, the step of preparing graphene oxide-supported calcium carbonate based on the graphene oxide comprises:
[0019] Add quicklime to hot water for digestion to obtain calcium hydroxide slurry;
[0020] Placing calcium hydroxide slurry in a reactor, adding a crystal nucleus inhibitor, the graphene oxide dispersion, and a crystallization directing agent into the reactor, introducing carbon dioxide gas at 50 to 100° C., and performing a carbonization reaction at 50 to 100° C.; wherein the graphene oxide dispersion is obtained by ultrasonically dispersing the graphene oxide;
[0021] When the pH of the reaction system drops to 7, the carbonization is continued for 15 minutes. After the reaction is completed, an intermediate slurry is obtained.
[0022] The intermediate slurry was heated to 80° C., a 3% sodium stearate solution was added and kept warm for 2 hours, and the mixture was filtered, dried and crushed to obtain the graphene oxide loaded calcium carbonate.
[0023] In another possible implementation, the crystal nucleus inhibitor is magnesium chloride.
[0024] In another possible implementation, the mass of the crystal nucleus inhibitor is 1‰ to 5‰ of the mass of the quicklime.
[0025] In another possible implementation, the crystal directing agent is a sodium hexametaphosphate solution with a concentration of 1% to 3%.
[0026] In another possible implementation, the mass of the crystallization directing agent is 1‰ to 5‰ of the mass of the quicklime.
[0027] In another possible implementation, the pre-curing time is 2 to 3 hours, and the temperature of the pre-curing room is 40 to 55°C.
[0028] The present application provides an autoclaved aerated concrete material, in which graphene oxide loaded calcium carbonate and graphene oxide are added, and the nucleation sites generated by the graphene oxide loaded calcium carbonate cause the deep microstructure of the material to directional generate a multi-level micro-nano structure similar to a "fiber" nano-needle, and the tip of the nano-needle structure splits out nanowires, which are filled in the capillaries and microscopic pores, effectively avoiding the appearance of the meniscus and increasing the density. The nanowires can further disperse the capillary pressure and reduce the capillary pressure difference, thereby avoiding drying shrinkage. Graphene oxide ions can reduce the attraction between the colloid particles and block the distance between the particles, thereby further avoiding drying shrinkage. Therefore, during the production, stacking and transportation process in high temperature in summer and ultra-low temperature in winter, the material provided by the present application can effectively solve the cracking problem caused by drying shrinkage, and improve the durability and service life of the material.
[0029] It is to be understood that the foregoing general description and the following detailed description are exemplary only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a flow chart of preparing autoclaved aerated concrete material provided in an embodiment of the present application;
[0031] Figure 2 It is a schematic diagram of a drying shrinkage test of the autoclaved aerated concrete materials prepared in Examples 1 to 3 and the comparative example provided in the examples of the present application;
[0032] Figure 3 It is a schematic diagram of a flexural strength test of the autoclaved aerated concrete materials prepared in Examples 1 to 3 and the comparative example provided in the embodiments of the present application;
[0033] Figure 4 It is a schematic diagram of a compressive strength test of the autoclaved aerated concrete materials prepared in Examples 1 to 3 and the comparative example provided in the embodiments of the present application. DETAILED DESCRIPTION
[0034] In order to make the technical solutions and advantages of the present application clearer, the implementation methods of the present application are described in further detail below.
[0035] On the one hand, an embodiment of the present application provides an autoclaved aerated concrete material, the autoclaved aerated concrete material comprising the following components in parts by weight:
[0036] 45-65 parts of fly ash, 3-10 parts of gypsum, 15-25 parts of solid waste slurry, 7-10 parts of cement, 9-13 parts of lime, 0.02-0.08 parts of aluminum paste, 0.001-0.005 parts of graphene oxide loaded with calcium carbonate, 0.001-0.005 parts of graphene oxide, and 0.005-0.01 parts of silicon powder.
[0037] Among them, the weight proportion of fly ash can be 45 parts, 48 parts, 50 parts, 52 parts, 55 parts, 58 parts, 60 parts, 62 parts, and 65 parts, the weight proportion of gypsum can be 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, and 10 parts, the weight proportion of solid waste slurry can be 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, and 25 parts, the weight proportion of cement can be 7 parts, 7.5 parts, 8 parts, 8.5 parts, 9 parts, 9.5 parts, and 10 parts, and the weight proportion of lime can be 9 parts, 9.5 parts, 10 parts, 10.5 parts, 11 parts, 11.5 parts, and 11.5 parts. 2 parts, 12.5 parts, and 13 parts by weight, the aluminum powder paste can be 0.02 parts, 0.03 parts, 0.04 parts, 0.05 parts, 0.06 parts, 0.07 parts, and 0.08 parts by weight, the graphene oxide loaded calcium carbonate can be 0.001 parts, 0.002 parts, 0.003 parts, 0.004 parts, and 0.005 parts by weight, the graphene oxide can be 0.001 parts, 0.002 parts, 0.003 parts, 0.004 parts, and 0.005 parts by weight, and the silicon powder can be 0.005 parts, 0.006 parts, 0.007 parts, 0.008 parts, 0.009 parts, and 0.01 parts by weight.
[0038] Drying shrinkage is mainly due to the formation of capillary pressure difference under the action of the surface tension of water and the meniscus. The material provided by this application adds graphene oxide loaded calcium carbonate and graphene oxide. The nucleation sites generated by the graphene oxide loaded calcium carbonate cause the deep microstructure of the material to directional generate a multi-level micro-nano structure of "fiber" nano needles, and the tip of the nano needle-like structure splits out nanowires, which are filled in the capillaries and microscopic pores, effectively avoiding the appearance of the meniscus and increasing the density. The nanowires can further disperse the capillary pressure and reduce the capillary pressure difference, thereby avoiding drying shrinkage. Graphene oxide ions can reduce the attraction between the colloid particles and block the distance between the particles, thereby further avoiding drying shrinkage. Therefore, during the production, stacking and transportation process in high temperature in summer and ultra-low temperature in winter, the material provided by this application can effectively solve the cracking problem caused by drying shrinkage and improve the durability and service life of the material.
[0039] In a possible implementation, the size of graphene oxide is 800 nm to 200 nm.
[0040] Among them, the size of graphene oxide can be 800nm, 700nm, 600nm, 500nm, 400nm, 300nm, and 200nm.
[0041] In the embodiments of the present application, the graphene oxide of the above-mentioned size can not only load nano-calcium carbonate, but also has a large specific surface area and super strong adsorption effect. The large number of oxygen-containing functional groups on the surface of the graphene oxide adsorb glass microbeads, which can reduce harmful pores, significantly improve the internal pore size distribution of the material, make the internal pores more dense and uniform, and significantly improve the tensile and bending strength of the material, reduce large capillary pores, thereby improving the mechanical properties, durability and drying shrinkage performance of the material.
[0042] On the other hand, the present invention provides a method for preparing an autoclaved aerated concrete material, see Figure 1 , the preparation method comprises:
[0043] Step 101: Prepare graphene oxide.
[0044] This step can be achieved by following the steps (1) to (3), including:
[0045] (1) 30 mL of concentrated sulfuric acid and 1 g of graphite were placed in a three-necked flask. The reaction temperature was controlled to be no higher than 5°C by an ice bath. A mixture of 12 g of potassium permanganate and 3 g of sodium nitrate was added to the three-necked flask. After reacting for 2 h, the temperature was raised to 60°C and the reaction was continued at 60°C for 9 h.
[0046] When adding the mixture of potassium permanganate and sodium nitrate into the three-necked flask, add it slowly in small amounts and multiple times, so as to effectively control the reaction temperature and avoid an overly rapid reaction.
[0047] (2) Add 150 mL of deionized water to a three-necked flask, raise the temperature to 85° C., and maintain the temperature for 30 min. Then, lower the reaction temperature to 40° C., and dropwise add 8 mL of hydrogen peroxide to obtain a mixed solution.
[0048] (3) After the mixed solution turns golden yellow, centrifugal precipitation and washing are performed until the pH value is 6.5-7.0 to obtain graphene oxide.
[0049] Step 102: Based on graphene oxide, prepare graphene oxide-loaded calcium carbonate.
[0050] This step can be achieved by following the steps (1) to (4), including:
[0051] (1) Quicklime is added into hot water for digestion to obtain calcium hydroxide slurry.
[0052] Quicklime is put into hot water at 80°C for digestion at a water-cement ratio of 1:2 to 1:5 to obtain crude calcium hydroxide slurry. After aging for 24 hours, it is sieved through a 200-mesh sieve to obtain refined calcium hydroxide slurry, which is the slurry in this step.
[0053] (2) placing calcium hydroxide slurry in a reactor, adding a crystal nucleus inhibitor, a dispersion of graphene oxide, and a crystallization directing agent into the reactor, introducing carbon dioxide gas at 50 to 100° C., and performing a carbonization reaction at 50 to 100° C.
[0054] Take 800 mL of calcium hydroxide slurry and place it in a 1 L glass reactor, add a nucleus inhibitor, a dispersion of graphene oxide, and a crystallization directing agent into the reactor, set a suitable carbonization starting temperature, i.e., 50-100°C, adjust a suitable stirring speed, and introduce carbon dioxide gas for carbonization reaction.
[0055] The carbonization starting point temperature may be 50°C, 60°C, 70°C, 80°C, 90°C, or 100°C.
[0056] In a possible implementation, the crystal nucleus inhibitor is magnesium chloride, and the mass of the crystal nucleus inhibitor is 1‰ to 5‰ of the mass of quicklime.
[0057] In this implementation, the mass of the crystal nucleus inhibitor can be 1‰, 2‰, 3‰, 4‰, or 5‰ of the mass of quicklime.
[0058] In the embodiment of the present application, the presence of magnesium ions causes the lattice distortion of calcium carbonate, thereby affecting and inhibiting the growth of its crystals. The metal ions occupy specific positions of calcium ions in the lattice, causing the lattice distortion of calcium carbonate, thereby changing the crystal structure and morphology of calcium carbonate, and causing the calcium carbonate to generate nano whisker calcium carbonate.
[0059] One thing that needs to be explained is that when Ca 2+ :Mg 2+ :CO3 2- When the ratio is 1:1:1, amorphous calcium carbonate will be produced.
[0060] In a possible implementation, the crystallization directing agent is a sodium hexametaphosphate solution with a concentration of 1% to 3%, and the mass of the crystallization directing agent is 1‰ to 5‰ of the mass of quicklime.
[0061] In this implementation, the crystallization directing agent can be a sodium hexametaphosphate solution with a concentration of 1%, a sodium hexametaphosphate solution with a concentration of 1.5%, a sodium hexametaphosphate solution with a concentration of 2%, a sodium hexametaphosphate solution with a concentration of 2.5%, or a sodium hexametaphosphate solution with a concentration of 3%, and the mass of the crystallization directing agent can be 1‰, 2‰, 3‰, 4‰, or 5‰ of the mass of quicklime.
[0062] In the embodiments of the present application, the presence of the crystal directing agent makes the nano-whisker calcium carbonate have a needle-like structure.
[0063] In a possible implementation, the graphene oxide dispersion is obtained by ultrasonically dispersing graphene oxide.
[0064] After graphene oxide is prepared, a certain amount of water may be added to the graphene oxide, and then ultrasonic dispersion may be performed to obtain a graphene oxide dispersion.
[0065] In the present embodiment, after graphene oxide is obtained, the graphene oxide can be divided into three parts, and then a certain amount of water is added to each part. Under the condition of ultrasonic power of 1800W, the ultrasonic time is controlled to be 30min, 60min and 90min respectively. The obtained graphene oxide dispersions are GO 30 ,GO 60 and GO 90 Different ultrasonic times will produce graphene oxide of different sizes, among which GO 30 The size of GO is 800nm. 60 The size of GO is 500nm. 90 The size is 200nm.
[0066] In a possible implementation, the volume of the introduced carbon dioxide can be determined according to quicklime, for example, the volume ratio of quicklime to carbon dioxide is 1:1 to 1:3.
[0067] (3) When the pH of the reaction system drops to 7, aeration and carbonization are continued for 15 minutes. After the reaction is completed, an intermediate slurry is obtained.
[0068] During the reaction, the pH of the reaction system can be measured. When the pH of the reaction system drops to 7, carbon dioxide gas is continuously introduced for 15 minutes. After the reaction is completed, an intermediate slurry is obtained.
[0069] (4) The intermediate slurry is heated to 80° C., a 3% sodium stearate solution is added and kept warm for 2 h, and then filtered, dried, and crushed to obtain graphene oxide loaded with calcium carbonate.
[0070] In a possible implementation, the mass of the sodium stearate solution may be 0.9%, 1%, or 1.1% of the mass of the intermediate slurry.
[0071] In the embodiment of the present application, sodium stearate is used as a surface modifier. The addition of sodium stearate can reduce the surface energy of calcium carbonate and increase its surface active groups, thereby improving the interaction between graphene oxide and calcium carbonate and enhancing the binding force between the two. In addition, the addition of sodium stearate also helps to disperse calcium carbonate, so that calcium carbonate is evenly dispersed on the surface of graphene oxide.
[0072] Step 103: According to the weight proportion of each component, fly ash, gypsum and solid waste slurry are wet-ground to obtain fly ash slurry, gypsum slurry and solid waste slurry.
[0073] Fly ash, gypsum and solid waste slurry are weighed separately and wet-grinded to make slurry, and the water-to-solid ratio is controlled at 0.53-0.55. The moisture content of the obtained slurry is 35%-41%, and the 80μm sieve residue fineness is 20%-30%.
[0074] The fly ash is grade three ash, the 80μm sieve fineness is 20%-25%, and the water content of fly ash slurry is 36%-40%.
[0075] The gypsum is desulfurized gypsum, and the water content of the gypsum slurry is 30% to 40%.
[0076] Solid waste slurry is obtained by mixing solid waste with water. The solid waste may include at least one of steel slag, mineral slag, magnesium slag, phosphorus slag, and carbide slag. Of course, solid waste also includes other types of waste, which is not specifically limited.
[0077] Step 104: Turn on the pouring mixer to preheat with steam, add fly ash slurry, gypsum slurry and solid waste slurry, then add graphene oxide-loaded calcium carbonate and graphene oxide, stir evenly, then add cement, lime, aluminum powder paste and silicon powder, stir evenly to obtain autoclaved aerated concrete slurry, and pour the autoclaved aerated concrete slurry into a mold.
[0078] The pouring mixer is turned on and preheated with steam for 10 seconds. After adding fly ash slurry, gypsum slurry and solid waste slurry, it is stirred at a uniform speed for 30 seconds. Then, graphene oxide-loaded calcium carbonate and graphene oxide are added and stirred for 50 to 60 seconds. Then, cement, lime, aluminum powder paste and silicon powder are added and stirred for 30 to 40 seconds to obtain autoclaved aerated concrete slurry, which is poured into a mold.
[0079] Among them, the lime is medium-speed lime, the effective calcium oxide is ≥75%, the digestion time is 8 to 15 minutes, and the digestion temperature is 99 to 101°C.
[0080] The cement is P·II 525 silicate cement that meets the requirements of "General Portland Cement" GB / T 175-2020, wherein the calcium silicate mineral content is ≥66%, and the mass ratio of CaO to SiO2 is ≥2.0.
[0081] Aluminum powder paste is mainly used as gas-generating material, with a solid content of ≥65% and an aluminum content of more than 90% in the solid part.
[0082] Step 105: placing a steel mesh cage into the mold, and performing aeration pre-curing, cutting, and autoclaving to obtain an autoclaved aerated concrete material.
[0083] Use clips to fix the steel mesh cage on the automatic circulation saddle with a steel bar, then insert it into the mold and pre-cure it in a pre-curing room at a temperature of 40-55°C for 2-3 hours. After the pre-curing is completed, pull out the steel bar and leave the steel mesh cage inside the embryo.
[0084] Among them, the temperature of the pre-curing room can be 40℃, 42℃, 45℃, 48℃, 50℃, 52℃, and 55℃, and the pre-curing time can be 2h, 2.1h, 2.2h, 2.3h, 2.4h, 2.5h, 2.6h, 2.7h, 2.8h, 2.9h, and 3h.
[0085] The pre-cured embryonic body is cut three times by milling grooves, longitudinal cutting and transverse cutting, and then turned over to remove the scraps on the surface and around the embryonic body. It is then sent to the autoclave for constant temperature and pressure autoclaving and curing for 6 hours. After the curing is completed, the autoclaved aerated concrete material is obtained.
[0086] The temperature in the autoclave may be 180°C ± 10°C, and the pressure may be 1.1 MPa ± 0.5 MPa.
[0087] The autoclaved aerated concrete material prepared by the method provided in this application has the following effects:
[0088] 1. The autoclaved aerated concrete material prepared in this application has extremely low drying shrinkage performance. Drying shrinkage is mainly due to the capillary pressure difference formed under the action of the surface tension of water and the meniscus. The nucleation sites generated by the graphene oxide-loaded calcium carbonate particles cause the deep microstructure of the material to directional generate a multi-level micro-nano structure similar to a "fiber" nano-needle, and the tip of the nano-needle structure splits out nanowires, which are filled in the capillaries and microscopic pores to effectively avoid the appearance of the meniscus and increase the density. The nanowires can further disperse the capillary pressure and reduce the capillary pressure difference, thereby avoiding drying shrinkage. Graphene oxide ions can reduce the attraction between the colloid particles and block the distance between the particles, thereby further avoiding drying shrinkage. During the production, stacking and transportation process in high temperature in summer and ultra-low temperature in winter, the material can effectively solve the cracking problem caused by drying shrinkage, improve the durability and service life of the material, and expand the application range of the material in special environments.
[0089] 2. The autoclaved aerated concrete material prepared in this application has excellent toughness. Under the synergistic effect of graphene oxide, graphene oxide loaded calcium carbonate and crystallization directing agent, its internal morphology is directed from the inside out to generate dense and uniform "fiber" nano needles and nano-filamentary multi-level micro-nano structures. When cracks occur, its "fiber" nano needle-like and filamentary multi-level micro-nano structures force the cracks to change their extension direction or become smaller cracks, which can solve the problem of crack expansion and prevent the occurrence of connected cracks.
[0090] 3. The graphene oxide prepared in the present application can not only load nano-calcium carbonate, but also has a large specific surface area and super strong adsorption effect. The large number of oxygen-containing functional groups on the surface of graphene oxide adsorb glass microbeads, which can reduce harmful pores, significantly improve the internal pore size distribution of reinforced concrete, make the pores inside the material more dense and uniform, and significantly improve the tensile and bending strength, reduce large capillary pores, thereby improving the mechanical properties, durability and drying shrinkage performance of the material.
[0091] 4. The autoclaved aerated concrete material prepared in this application has a low water absorption rate. Since a large amount of graphene oxide loaded with calcium carbonate further fills the pores, water molecules are prevented from entering the internal microscopic pores and capillaries, the water absorption is reduced, and the drying shrinkage and cracking are further prevented.
[0092] The technical solution of the present application will be described in detail below through specific embodiments.
[0093] In the following specific examples, the operations involved, if the conditions are not specified, are all carried out under conventional conditions or conditions recommended by the manufacturer. The raw materials used, if the manufacturers and specifications are not specified, are all conventional products that can be obtained from the market.
[0094] Example 1
[0095] Step 1: Preparation of raw materials: 1824.5 kg of fly ash, 209 kg of gypsum and 573 kg of solid waste slurry are placed in a ball mill for wet grinding to form slurry. The obtained slurry has a moisture content of 38%, a particle size of 80 um and a sieve residue fineness of 24%.
[0096] Step 2: Slurry preparation and pouring: Add 33kg of graphene oxide loaded calcium carbonate, 3kg of graphene oxide GO into the slurry in sequence. 90 and 30kg of silicon powder, stir again for 60s; then add 246kg of cement and 298kg of lime, stir for 40s, and finally add 3kg of aluminum powder paste, evenly disperse for 35s to form a slurry, and then pour the slurry into a carbon steel mold coated with release oil.
[0097] Among them, graphene oxide supported calcium carbonate is on graphene oxide GO 90 Obtained by loading calcium carbonate on.
[0098] Step 3: Insert the steel bar: Use the buckle to fix the steel mesh cage on the automatic circulation saddle with steel bar, and then insert it into the carbon steel mold containing the slurry.
[0099] Step 4: Pre-curing and quiescence: Place the slurry in a pre-curing and quiescence room with a constant temperature of 45°C. After 140 minutes, the autoclaved aerated concrete body is obtained. After the aeration pre-curing is completed, the steel bar is pulled out and the steel mesh cage is left inside the body.
[0100] Step 5: Cutting and turning: Transfer the pre-cured embryo to the side panel for milling, longitudinal cutting and cross cutting to cut into embryos with a size of 2400mm*600mm*240mm. After cutting, use a crane to turn the embryo over and remove the scraps on the upper and lower surfaces and around.
[0101] Step 6: Autoclave curing: Place the ground-turned embryo on a trolley in front of the autoclave and send it to the autoclave for autoclave curing at 180°C ± 10°C and 1.1MPa ± 0.5MPa for 6 hours. After curing, the autoclaved aerated concrete material is obtained.
[0102] Example 2
[0103] Step 1: Preparation of raw materials: 1824.5 kg of fly ash, 209 kg of gypsum and 573 kg of solid waste slurry are placed in a ball mill for wet grinding to form slurry. The obtained slurry has a moisture content of 38%, a particle size of 80 um and a sieve residue fineness of 24%.
[0104] Step 2: Slurry preparation and pouring: Add 33kg of graphene oxide loaded calcium carbonate, 3kg of graphene oxide GO into the slurry in sequence. 60and 30kg of silicon powder, stir again for 60s; then add 246kg of cement and 298kg of lime, stir for 40s, and finally add 3kg of aluminum powder paste, evenly disperse for 35s to form a slurry, and then pour the slurry into a carbon steel mold coated with release oil.
[0105] Among them, graphene oxide supported calcium carbonate is on graphene oxide GO 60 Obtained by loading calcium carbonate on.
[0106] Step 3: Insert the steel bar: Use the buckle to fix the steel mesh cage on the automatic circulation saddle with steel bar, and then insert it into the carbon steel mold containing the slurry.
[0107] Step 4: Pre-curing and quiescence: Place the slurry in a pre-curing and quiescence room with a constant temperature of 45°C. After 140 minutes, the autoclaved aerated concrete body is obtained. After the aeration pre-curing is completed, the steel bar is pulled out and the steel mesh cage is left inside the body.
[0108] Step 5: Cutting and turning: Transfer the pre-cured embryo to the side panel for milling, longitudinal cutting and cross cutting to cut into embryos with a size of 2400mm*600mm*240mm. After cutting, use a crane to turn the embryo over and remove the scraps on the upper and lower surfaces and around.
[0109] Step 6: Autoclave curing: Place the ground-turned embryo on a trolley in front of the autoclave and send it to the autoclave for autoclave curing at 180°C ± 10°C and 1.1MPa ± 0.5MPa for 6 hours. After curing, the autoclaved aerated concrete material is obtained.
[0110] Example 3
[0111] Step 1: Preparation of raw materials: 1824.5 kg of fly ash, 209 kg of gypsum and 573 kg of solid waste slurry are placed in a ball mill for wet grinding to form slurry. The obtained slurry has a moisture content of 38%, a particle size of 80 um and a sieve residue fineness of 24%.
[0112] Step 2: Slurry preparation and pouring: Add 33kg of graphene oxide loaded calcium carbonate, 3kg of graphene oxide GO into the slurry in sequence. 30 and 30kg of silicon powder, stir again for 60s; then add 246kg of cement and 298kg of lime, stir for 40s, and finally add 3kg of aluminum powder paste, evenly disperse for 35s to form a slurry, and then pour the slurry into a carbon steel mold coated with release oil.
[0113] Among them, graphene oxide supported calcium carbonate is on graphene oxide GO 30 Obtained by loading calcium carbonate on.
[0114] Step 3: Insert the steel bar: Use the buckle to fix the steel mesh cage on the automatic circulation saddle with steel bar, and then insert it into the carbon steel mold containing the slurry.
[0115] Step 4: Pre-curing and quiescence: Place the slurry in a pre-curing and quiescence room with a constant temperature of 45°C. After 140 minutes, the autoclaved aerated concrete body is obtained. After the aeration pre-curing is completed, the steel bar is pulled out and the steel mesh cage is left inside the body.
[0116] Step 5: Cutting and turning: Transfer the pre-cured embryo to the side panel for milling, longitudinal cutting and cross cutting to cut into embryos with a size of 2400mm*600mm*240mm. After cutting, use a crane to turn the embryo over and remove the scraps on the upper and lower surfaces and around.
[0117] Step 6: Autoclave curing: Place the ground-turned embryo on a trolley in front of the autoclave and send it to the autoclave for autoclave curing at 180°C ± 10°C and 1.1MPa ± 0.5MPa for 6 hours. After curing, the autoclaved aerated concrete material is obtained.
[0118] Application Examples
[0119] This application example tests the autoclaved aerated concrete materials prepared in Examples 1 to 3 and the comparative example and the autoclaved aerated concrete materials in the related art. Among them, graphene oxide and graphene oxide-loaded calcium carbonate are not added to the autoclaved aerated concrete material in the comparative example, and the rest of the composition is the same as that of Examples 1 to 3.
[0120] See also Figure 2 , Figure 2 Schematic diagram of drying shrinkage test of autoclaved aerated concrete materials prepared in Examples 1 to 3 and Comparative Example. Figure 2 It can be seen that the drying shrinkage value of the autoclaved aerated concrete material prepared in the comparative example is 5.6×10 -4 m / m, while the drying shrinkage values of the autoclaved aerated concrete materials prepared in Examples 1 to 3 were 8×10 -6 m / m, 13×10 -6 m / m, 11×10 -6 m / m, the drying shrinkage value is reduced by two orders of magnitude.
[0121] This is because the graphene oxide loaded calcium carbonate and the nucleation sites generated by graphene oxide cause changes in the deep microstructure of the material, and act as a nucleating agent for calcium silicate hydrate CSH, which converts the CSH gel into tobermorite crystals, increases its crystallinity, and further reduces the CSH gel content. The microscopic morphology of graphene oxide loaded calcium carbonate is a dense and uniform nano-needle multi-level micro-nano structure. At the same time, nanoparticles can fill the capillary pores of CSH gel, prevent the entry of gel water, improve compaction and reduce porosity, and prevent the spread of fine cracks, thereby greatly reducing the drying shrinkage performance of autoclaved aerated concrete materials.
[0122] See also Figure 3 , Figure 3 This is a schematic diagram of the flexural strength test of the autoclaved aerated concrete materials prepared in Examples 1 to 3 and the comparative example. Figure 3 It can be seen that the flexural strength of the autoclaved aerated concrete material prepared in the comparative example is 0.15 MPa, while the flexural strengths of the autoclaved aerated concrete materials prepared in Examples 1 to 3 are 0.28 MPa, 0.25 MPa, and 0.23 MPa, respectively, and the flexural strength is greatly improved.
[0123] This is because the microscopic morphology of graphene oxide loaded calcium carbonate is a denser and more uniform nano-needle-shaped multi-level micro-nano structure. When a crack occurs, when the crack tip contacts the nano-whisker calcium carbonate particle, its needle-shaped multi-level micro-nano structure forces the crack to change its extension direction or become a smaller crack, which can effectively alleviate the expansion of the crack and prevent the appearance of connected cracks, thus having excellent flexural resistance.
[0124] See also Figure 4 , Figure 4 This is a schematic diagram of the compressive strength test of the autoclaved aerated concrete materials prepared in Examples 1 to 3 and the comparative example. Figure 4 It can be seen that the compressive strength of the autoclaved aerated concrete material prepared in the comparative example is 5.0 MPa, while the compressive strengths of the autoclaved aerated concrete materials prepared in Examples 1 to 3 are 6.3 MPa, 5.9 MPa, and 5.8 MPa, respectively, and the compressive strength is also greatly improved.
[0125] This is because after adding graphene oxide loaded with calcium carbonate, the pore structure of the material becomes dense and uniform, so the compressive strength is improved to a certain extent and meets the national standards for autoclaved aerated concrete materials.
[0126] The above description is only for the purpose of facilitating those skilled in the art to understand the technical solution of the present application and is not intended to limit the present application. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. An autoclaved aerated concrete material, characterized in that: The autoclaved aerated concrete material comprises the following components in parts by weight: 45-65 parts of fly ash, 3-10 parts of gypsum, 15-25 parts of solid waste slurry, 7-10 parts of cement, 9-13 parts of lime, 0.02-0.08 parts of aluminum paste, 0.001-0.005 parts of graphene oxide loaded with calcium carbonate, 0.001-0.005 parts of graphene oxide, and 0.005-0.01 parts of silicon powder.
2. The autoclaved aerated concrete material according to claim 1, characterized in that: The size of the graphene oxide is 800nm-200nm.
3. A method for preparing the autoclaved aerated concrete material according to any one of claims 1 to 2, characterized in that: The preparation method comprises: preparing graphene oxide; Based on the graphene oxide, preparing graphene oxide-loaded calcium carbonate; According to the weight proportion of each component, fly ash, gypsum and solid waste slurry are wet-grinded to obtain fly ash slurry, gypsum slurry and solid waste slurry; Turn on the pouring mixer to preheat with steam, add the fly ash slurry, the gypsum slurry and the solid waste slurry, then add the graphene oxide-loaded calcium carbonate and the graphene oxide, stir evenly, then add cement, lime, aluminum powder paste and silicon powder, stir evenly to obtain autoclaved aerated concrete slurry, and pour the autoclaved aerated concrete slurry into a mold; A steel mesh cage is placed in the mold, and the autoclaved aerated concrete material is obtained through gasification pre-curing, cutting, and autoclaving.
4. The preparation method according to claim 3, characterized in that: The preparation method of the graphene oxide comprises: 30 mL of concentrated sulfuric acid and 1 g of graphite were placed in a three-necked flask, and the reaction temperature was controlled to be no higher than 5° C. by an ice bath. A mixture of 12 g of potassium permanganate and 3 g of sodium nitrate was added to the three-necked flask, and the mixture was reacted for 2 h, and then the temperature was raised to 60° C., and the reaction was continued at 60° C. for 9 h. Add 150 mL of deionized water to the three-necked flask, raise the temperature to 85° C., and maintain for 30 min, then lower the reaction temperature to 40° C., and drop 8 mL of hydrogen peroxide to obtain a mixed solution; After the mixed solution turns into golden yellow, centrifugal precipitation and washing are performed until the pH value is 6.5-7.0 to obtain the graphene oxide.
5. The preparation method according to claim 3 or 4, characterized in that: The method of preparing graphene oxide-supported calcium carbonate based on the graphene oxide comprises: Add quicklime to hot water for digestion to obtain calcium hydroxide slurry; Placing calcium hydroxide slurry in a reactor, adding a crystal nucleus inhibitor, the graphene oxide dispersion, and a crystallization directing agent into the reactor, introducing carbon dioxide gas at 50 to 100° C., and performing a carbonization reaction at 50 to 100° C.; wherein the graphene oxide dispersion is obtained by ultrasonically dispersing the graphene oxide; When the pH of the reaction system drops to 7, the carbonization is continued for 15 minutes. After the reaction is completed, an intermediate slurry is obtained. The intermediate slurry was heated to 80° C., a 3% sodium stearate solution was added and kept warm for 2 hours, and the mixture was filtered, dried and crushed to obtain the graphene oxide loaded calcium carbonate.
6. The preparation method according to claim 5, characterized in that: The crystal nucleus inhibitor is magnesium chloride.
7. The preparation method according to claim 5 or 6, characterized in that: The mass of the crystal nucleus inhibitor is 1‰ to 5‰ of the mass of the quicklime.
8. The preparation method according to claim 5, characterized in that: The crystal directing agent is a sodium hexametaphosphate solution with a concentration of 1% to 3%.
9. The preparation method according to claim 5 or 8, characterized in that: The mass of the crystal directing agent is 1‰ to 5‰ of the mass of the quicklime.
10. The preparation method according to claim 3, characterized in that: The pre-curing time is 2 to 3 hours, and the temperature in the pre-curing room is 40 to 55°C.
Citation Information
Cited By
Multi-solid waste synergic autoclaved aerated concrete material and preparation method thereof
CN122940426A
